Sinergi Literasi Al-Qur’an dan Dakwah Partisipatif di Desa Sambueja: The Synergy of Qur’anic Literacy and Participatory Da’wah in Sambueja Village - Muhammad Yusram; Muhammad, Muhammad; Azwar, Azwar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PkM) was implemented in response to the low level of Qur’anic literacy across age groups and the weak local da‘wah cadre regeneration in Sambueja Village, Maros Regency. Conducted through the Community Service Program (KKN) of students from the Institut Agama Islam (IAI) STIBA Makassar, the program aims to enhance cross-generational Qur’anic literacy while strengthening mosque-based local da‘wah cadre development. The implementation employed a community-based participation approach, actively involving community members from the stages of planning and implementation through to evaluation. The results demonstrate a significant improvement in Qur’anic reading proficiency among Dirosa participants, high levels of enthusiasm among children attending Qur’anic Learning Centers (TPQ), and the emergence of young cadres who have begun to assume active roles in religious activities, including serving as imams, khatibs, and preachers. Furthermore, the Mosque Management Board (DKM) and the village government expressed strong commitment to sustaining the program beyond the KKN period. Overall, this initiative contributes to strengthening religious literacy, expanding community participation in da‘wah activities, and establishing a sustainable mosque-based empowerment model for religious rural communities.